Leukotriene C4 as a mediator of luteinizing hormone release from rat anterior pituitary cells. - Hulting, A L (1985)
This study demonstrates that leukotriene C4, at concentrations in the picomolar range, released luteinizing hormone (LH) but not growth hormone (GH) from dispersed rat anterior pituitary cells. Leukotriene B4, another lipoxygenase pathway product of arachidonic acid, had no effect on LH or GH release. The stimulatory effect of leukotriene C4 could be seen after 0.5 but not after 3 hr of incubation. This was in contrast to the dose-dependent LH-releasing hormone (LHRH)-induced LH release that was not measurable after 0.5 hr but was fully established after incubation for 3 hr. Furthermore, the LH-releasing ability of leukotriene C4 was blocked in the presence of high doses of LHRH. The immunohistochemical analysis revealed leukotriene C4-immunoreactive fibers at all levels of the median eminence, mainly in the lateral parts. These fibers exhibited a marked overlap distribution with LHRH-immunoreactive fibers and elution-restaining experiments revealed identity of at least a large proportion of the leukotriene C4- and LHRH-immunoreactive fibers. Furthermore, cell bodies in the preoptic area contained both leukotriene C4- and LHRH-like immunoreactivities, suggesting localization of these two compounds in the same neurons.